Ethical issues in laryngology: Tracheal stenting as palliative care. (15th January 2014) - Kazi, Aasif A.; Flowers, W. Jeffrey; Barrett, Jeanna M.; O'Rourke, Ashli K.; Postma, Gregory N.; Weinberger, Paul M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To improve understanding of aspects of end‐of‐life care that may not be intuitive to the otolaryngology community. Data Sources and Review Methods A comprehensive review of the literature was performed by searching Medline, Embase, and Google Scholar databases. Primary manuscripts' bibliographies were reviewed to identify any nonindexed references. Prospective consultation by means of one‐on‐one interviews was sought from nonotolaryngology key stakeholders in the areas of hospice nursing care and patient advocacy in order to identify pertinent issues. Results We identified over 1, 000 articles published from 1965 to 2013 on the topic of tracheal stents, as well as over 40, 000 on hospice/end‐of‐life care. Three articles focusing specifically on palliative care and airway stenting were identified, of which three were case reports and none were definitive reviews. There are a number of significant issues and concepts unique to hospice care. These are likely unfamiliar to all except for head and neck oncology‐specialized otolaryngologists. An example is that hospice care focuses on quality of life rather than prolongation of life (such as curative surgery). Patients with nonoperable tracheal obstruction from malignancy face an unpleasant demise from suffocation. For those patients, stenting can relieve suffering by restoring airway patency. Conclusions Airway stenting can be a valid palliative care option, even for terminal patients receiving hospice care, when performed to relieve airway obstruction and improve quality of life. End‐of‐life ethics is an underdeveloped area of otolaryngology that should be explored. Laryngoscope, 124:1663–1667, 2014